2009
DOI: 10.1007/s00787-008-0710-z
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between youth-reported and parent-reported psychopathology in a referred sample

Abstract: Objective: The study examined parent-youth agreement regarding reports on psychopathology among adolescents suffering from psychiatric disorders. Method: A total of 1,718 patients between the age of 11 and 18, as well as their parents, were assessed using the child behavior checklist (CBCL), and the youth self-report (YSR). Results: Poor to low agreement between parent- and adolescent-reported problem behavior on the internalizing scale, the total problem scale and moderate agreement concerning the externalizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
103
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 41 publications
9
103
2
2
Order By: Relevance
“…Both parents and children thus filled out a rating scale about the childrenÕs emotional symptoms and behavioural problems. However, several studies, carried out before and after the current study, have shown that there is a low correlation between the parentsÕ ratings and the childrenÕs self-ratings of their psychological problems (144)(145)(146)(147), which applies to refugee populations as well (148,149).…”
Section: Mental Health and Its Determinants 8-9 Years After Arrival Imentioning
confidence: 56%
“…Both parents and children thus filled out a rating scale about the childrenÕs emotional symptoms and behavioural problems. However, several studies, carried out before and after the current study, have shown that there is a low correlation between the parentsÕ ratings and the childrenÕs self-ratings of their psychological problems (144)(145)(146)(147), which applies to refugee populations as well (148,149).…”
Section: Mental Health and Its Determinants 8-9 Years After Arrival Imentioning
confidence: 56%
“…Second, agreement on child psychopathology assessment appears to vary according to the nature of a child's problems. Parent-child concordance appears to be better for externalizing symptoms and observable behaviors than for internalizing or internal states (Salbach-Andrae et al, 2009). In a study with male adolescents, parents, and teachers, the parent-adolescent concordance in externalizing symptoms was higher than internalizing symptoms, whereas parent-teacher or teacher-adolescent agree-ments regarding internalizing and externalizing symptoms were not significantly different (Youngstrom et al, 2000).…”
mentioning
confidence: 89%
“…More specifically, adaptive and maladaptive ER strategies were measured in our study on the basis of child's selfreport, while temperamental reactivity and depressive symptoms were measured by using mother's report. An alternative possible explanation is that the social desirability or ignorance prevented the mothers from reporting accurately on their children's depressive symptoms, leading to underreporting (Salbach-Andrae et al 2009). Nevertheless, we can conclude that the results of our study, in combination with previous findings, underline the need of further longitudinal research with multi-method and multiinformant designs to provide a clear understanding of ER and its role in the relationship between temperamental reactivity and depressive symptoms in adolescents.…”
Section: Temperamental Reactivity Er Strategies and Depressive Sympmentioning
confidence: 99%